2010
DOI: 10.1007/s10689-010-9343-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and clinical experience of physicians regarding preimplantation genetic diagnosis for hereditary cancer predisposition syndromes

Abstract: Approximately 5-10% of cancers are caused by an inherited predisposition. Individuals affected by hereditary cancer are often concerned about transmitting a predisposition to cancer to their children. Preimplantation genetic diagnosis (PGD) is a technology that allows embryos without a deleterious mutation associated with a hereditary cancer syndrome to be identified and implanted. The aim of this study is to assess the knowledge, attitudes, and clinical experience of physicians regarding PGD for hereditary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…In the United States, approximately half of gynaecological oncologists and obstetric/gynaecologists surveyed thought PGD appropriate for BRCA; o20% reported that they were 'knowledgeable' or 'very knowledgeable' about PGD. 25 Interestingly, the proportions of surveyed health professionals who consider PGD acceptable are consistent with the proportions who view PND/TOP as acceptable for the same conditions. In the United Kingdom, data from clinical genetics units are lacking.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In the United States, approximately half of gynaecological oncologists and obstetric/gynaecologists surveyed thought PGD appropriate for BRCA; o20% reported that they were 'knowledgeable' or 'very knowledgeable' about PGD. 25 Interestingly, the proportions of surveyed health professionals who consider PGD acceptable are consistent with the proportions who view PND/TOP as acceptable for the same conditions. In the United Kingdom, data from clinical genetics units are lacking.…”
Section: Discussionsupporting
confidence: 55%
“…22 PGD for cancer predisposition divides opinion among health professionals in Europe 17,23 and the United States. 24,25 Attitudes among people at risk of cancer towards PGD are similarly mixed. [26][27][28] However, all of these studies have been conducted with women of all age groups -for the majority of respondents, age may preclude having (further) children, and some studies include women who do not have a BRCA mutation and so would not be able to use PGD.…”
Section: Introductionmentioning
confidence: 99%
“…The question of which healthcare provider(s) should be approaching patients with information about PGD is important to consider. It is notable that patients most often preferred to have these discussions with a genetic counselor or with the physician in charge of syndrome management, however not all patients may have access to a genetic counselor and previous data have suggested that physician knowledge of PGD for hereditary cancer is limited[38]. Given the high degree of ambivalence about PGD that we observed in this population, continuing education may be indicated to ensure that providers have sufficient knowledge about PGD so that patients can make informed decisions about whether to seek more specialized reproductive counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Rb is a high-penetrance disease of early childhood, and therefore parents of an affected child with Rb may still be in the reproductive age at the time of diagnosis of an affected child and may opt for PND in a subsequent pregnancy. Furthermore, physicians caring for patients with childhood cancer often have more intense contact with the family and will have more awareness of a possible impact of childhood cancer on family planning and be more knowledgeable about reproductive options than physicians caring for adult-onset cancer patients [31]. Differences in uptake may also be explained by the lack of risk-reducing options for the hereditary cancer syndromes with childhood-onset, apart from screening to detect cancer at an early stage [32].…”
Section: Discussionmentioning
confidence: 99%